Promoting Healthy Relationship Development in Teens, Part II: Three Key Qualities to Foster Better Relationships - Victor W. Harris; Gilon Marts; Muthusami Kumaran (EDIS)
Getting married and staying married require a complicated calculus of factors that must come together to produce healthy and satisfying relationships. While couple interactional processes tend to be the most predictive of whether or not they will stay together and find happiness, background and contextual factors and individual traits also factor heavily into the equation. Finding two socks that match (and don’t wear out) is much more likely to occur when the relationship is based upon a deep and enduring friendship. Asking the question, “Will this choice enhance or diminish my marital friendship?” and then choosing to make the choices that will enhance the marital friendship more often than not are healthy strategies for success. This 5-page fact sheet was written by Victor W. Harris, Gilon Marts, and Muthusami Kumaran, and published by the UF Department of Family Youth and Community Sciences, March 2013.